S1P lyase inhibition improves post-ischemic cardiac remodeling independently of infarct size via S1P receptor 1. (3rd October 2022) - Polzin, A; Dannenberg, L; Benckhoff, M; Barcik, M; Keul, P; Weske, S; Ahlbrecht, S; Helten, C; Haberkorn, S; Floegel, U; Zeus, T; Mueller, T; et al.
Abstract: Background: Revascularization of the infarct vessel is the golden standard in acute myocardial infarction (AMI). Even in Western countries, more than ten percent of AMI patients are so-called "latecomers" and it is controversial if revascularization of the infarct vessel is beneficial in these patients. Current guidelines even discourage revascularization of the infarcted artery if symptom onset was >48 hours and the patient is asymptomatic. These patients are at high risk for cardiovascular events and heart failure with reduced ejection fraction (HFrEF). HFrEF has an enormous socio-economic impact, high morbidity, and mortality. Purpose: Therapeutic options targeting post-ischemic cardiac remodeling are sparse. The bioactive sphingolipid sphingosine-1-phosphate (S1P) reduces ischemia/reperfusion injury when administered in advance. However, its impact on post-ischemic remodeling independently of its infarct size (IS)-reducing effect is yet unknown. Methods: Acute myocardial infarction (AMI) in mice was induced by permanent ligation of the left anterior descending artery (LAD). C57Bl/6J were treated with the S1P lyase inhibitor 4-deoxypyridoxine (DOP) starting seven days prior to AMI to increase endogenous S1P concentrations. Cardiac function and myocardial healing were assessed by cardiovascular magnetic resonance imaging (cMRI), histomorphology and gene expression analysis. DOP effects were investigated in cardiomyocyte-specific S1P receptor 1 deficient (S1PR1 Cardio Cre+ and Cre− control) mice, and S1P concentrations measured by LC-MS/MS. Results: S1P concentrations in plasma before induction of AMI were increased fourfold by DOP (Control 0.97±0.09μM [n=6] vs. DOP 3, 80±0, 09μM [n=6]). Scar size determined by MRI, as well as ejection fraction (EF), did not differ 24 h post AMI. In contrast, after 21 days, there was a clear difference between the two groups (scar size vehicle: 19.3±6.2% vs. DOP 13.4±5.7%; EF: Vehicle: 26.4±8.7% vs. DOP 38.2±11.8%). In addition, in the remote area 21 days post AMI in the DOP-treated animals, a reduced gene expression of brain natriuretic peptide, atrial natriuretic peptide and collagen 1a2. Finally, cardiomyocyte diameter in the remote myocardium was 21% smaller in DOP-treated (Vehicle: 21.95±1.59μm vs. DOP 17.35±0.77μm). The benefit of DOP-treatment was abolished in cardiomyocyte-specific S1PR1-deficient mice. Conclusion: S1P improves cardiac function and myocardial healing post AMI independently of initial infarct size via S1PR1. Hence, in addition to its beneficial effects on I/R injury, S1PR1 may be a promising target in post-infarction myocardial remodeling as adjunctive therapy to revascularization and in patients who are not eligible for standard interventional procedures. Funding Acknowledgement: Type of funding sources: None.